Karakteristik Multitemporal Arus Permukaan Laut di Perairan Tuban, Jawa Timur - Muhammad Tezar; Mifta Irmayunita; Ahmad Mualim; Faruq Faruq; Luhur Moekti Prayogo (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2023)
Sea currents are the mass transfer of water from one place to another caused by wind, density differences, and tides. In general, the characteristics of ocean currents in Indonesian waters are influenced by wind and tides. In shallow waters (coastal areas), ocean currents can be generated by ocean waves, wind, and tides. Meanwhile, tides are the main driving force in narrow and semi-enclosed waters (straits and bays). This study aims to determine the multitemporal differences in current movement patterns in 2010-2012 in the waters of Tuban, East Java. Research data is obtained from NOAA and calculated direction and speed, and then the results are presented in the form of a map. From the research results that have been done, it can be concluded that the current velocity in the waters of Tuban in 2010-2012 is relatively the same (the difference in current speed is not significant). In 2010 and 2011, the average current speed was 0.06 m/s, where the current moved from west to east and north. Then in 2012, the average current speed was 0.11 m/s, where the current moved from west to east. It is necessary to conduct a more in-depth study to determine the effect of tides on current movement, especially in shallow waters. In addition, further research is expected to use data from survey results directly in the field for validation so that research results will be more accurate.